Immune interferon inhibits proliferation and induces 2'-5'-oligoadenylate synthetase gene expression in human vascular smooth muscle cells. - Warner, S J (1989)
Proliferation of vascular smooth muscle cells (SMC) contributes to formation of the complicated human atherosclerotic plaque. These lesions also contain macrophages, known to secrete SMC mitogens, and T lymphocytes. Many of the SMC in the lesions express class II major histocompatibility antigens, an indication that activated T cells secrete immune IFN-gamma locally in the plaque. We therefore studied the effect of IFN-gamma on the proliferation of cultured SMC derived from adult human blood vessels. IFN-gamma (1,000 U/ml) reduced [3H]thymidine (TdR) incorporation into DNA by SMC stimulated with the well-defined mitogens IL 1 (from 15.3 +/- 0.7 to 6.2 +/- 0.7 dpm X 10(-3)/24 h) or platelet-derived growth factor (PDGF) (from 18.5 +/- 1.0 to 7.3 +/- 0.7 dpm X 10(-3)/24 h). Kinetic and nuclear labeling studies indicated that this effect of IFN-gamma was not due to altered thymidine transport or specific radioactivity of TdR in the cell. In longer term experiments (4-16 d) IFN-gamma prevented net DNA accumulation by SMC cultures stimulated by PDGF. IFN-gamma also delayed (from 30 to 60 min) the time to peak level of c-fos RNA in IL 1-treated SMC. It is unlikely that cytotoxicity caused these effects of IFN-gamma, as the inhibition of growth was reversible and we detected no cell death in SMC cultures exposed to this cytokine. Activation of 2'-5' oligoadenylate synthetase gene expression may mediate certain antiproliferative and antiviral effects of interferons. Both IFN-gamma and type I IFNs (IFN-alpha or IFN-beta) induced 2'-5' oligoadenylate synthetase mRNA and enzyme activity in SMC cultures, but with concentration dependence and time course that may not account for all of IFN-gamma's cytostatic effect on SMC. The accumulation of SMC in human atherosclerotic lesions is a long-term process that must involve altered balance between growth stimulatory and inhibitory factors. The cytostatic effect of IFN-gamma on human SMC demonstrated here may influence this balance during human atherogenesis, because T cells present in the complicated atherosclerotic plaque likely produce this cytokine.